Responsibility of Airline For Civil Aviation Safety For Dangerous Materials and Goods in Aircraft - Budi Bahreisy; Hidayat Hidayat; Ferdy Saputra (DE LEGA LATA: JURNAL ILMU HUKUM, 2022)
Air transportation is an aviation system that involves many parties. Implementation of aviation safety needs to be implemented in all sectors. This journal aimed to find out whether the cargo of hazardous materials or goods was meant, how the duties and obligations of airlines to the safety of civil aviation for hazardous materials and goods in aircraft, and how the airline's responsibility to the safety of civil aviation for materials and dangerous goods in the aircraft. The type of research in this journal was normative legal research. The approach in this journal writing used the approach of law (statue approach). The results showed that the Minister of Transportation Regulation No. 77 of 2011 Chapter II on the type of air transport accountability and the amount of compensation. Article 2 says carriers using aircraft shall be liable for losses to: Passengers dying, permanently disfigured or injured; Lost and damaged cabin baggage; Destroyed, or destroyed checked baggage; Destroyed, or damaged cargo; Air freight delays and losses suffered by third parties. Therefore the responsibility of airline in this case the airline is to start up to the downing of aircraft passengers